Analysis on the estimation errors of the lowest and highest astronomical tides for the southwestern 2.5 GW offshore wind farm, Korea - Dong Hui Ko; Shin Taek Jeong; Hong-Yeon Cho; Keum-Seok Kang (International Journal of Naval Architecture and Ocean Engineering, 2018)
For the design of wind-power facilities, the highest and lowest astronomical tides (HAT and LAT, respectively) are needed for the tidal-water levels regarding international designs; however, the approximate highest high water and approximate lowest low water AHHW and ALLW, respectively, have been used in Korea. The HAT and LAT in the wind-farm test-bed sea should be estimated to satisfy the international standard. In this study, the HAT and LAT are therefore estimated using the hourly tidal-elevation data of the Eocheongdo, Anmado, Younggwang, Gunsan, Janghang, and Seocheon tidal-gauging stations that are located in the adjacent coastal sea. The nodal variation patterns of the major lunar components, such as M2, O1, and K1 are analyzed to check the expected long-term lunar cycle, i.e., 18.61 year's nodal-variation patterns. The temporal amplitude variations of the M2, O1, and K1 clearly show the 18.61-years periodic patterns in the case of the no-nodal correction condition. In addition, the suggested HAT and LAT elevations, estimated as the upper and lower confidence limits of the yearly HAT and LAT elevations, are 50 cm greater than the AHHW and 40 cm lower than the ALLW, respectively.